Optimalisasi Usaha Agroindustri Sagu di Kecamatan Saparua Kabupaten Maluku Tengah - Ester Dorina Leatemia (CV. Publikasi Indonesia, 2022)
This research aimed to know allocation usage of optimal resource for bagea and sarut, and to describe the factor influence development bagea and sarut industries. This research used case study method to 30 entrepreneurs of bagea and sarut in the Ihamahu village, sub district of the Saparua, regency of the middle Mollucas. The consist of entrepreneur be based on supplement raw material were type I, namely canary bagea and canary sarut (17 people), and type II, namely coconut bagea and coconut sarut (13 people). The research result showed that for type I, at optimal strategy of sago flour and woman work hours did not remain or to used up, where as canary, man work hours and capital did not all used and still remain each 0,01 kg of canary, 0,01 man work hours and also capital of Rp 92,00. For type II, at optimal strategy need entire capital, so the capital did not remain. The other resources did not used up were sago flour of 1.210,52 kg, coconut of 1.268,56 kg, 194,79 man work hours, and 1.831,03 woman work hours. The factors influenced development bagea and sarut industries were capital, availability of sago flour, the high price of sago flour, the product (the kind of product), the competitors in marketing of bagea and sarut product, the market and payment of selling bagea and sarut was credit, the human resource of low (the level of education) and inexistence arrangement of job.